The Avifauna of Mt. Haponhaponon, Mantikil, Siaton, Negros Oriental, with notes on other vertebrates (2009)
Preliminary results on the surveys of the vertebrate fauna of Mt. Haponhaponon are presented. A total of 91 species of birds are known in the Mantikil area, 84 species of which are confirmed by this study. Some of the birds confirmed are conservation interest. A few mammalian, reptilian and amphibian fauna were also noted. Continued clearing of the forest for agriculture is the prevalent threat to these resources.
Keywords: Vertebrates; Mt. Haponhaponon (Negros Oriental)